2010
DOI: 10.1252/jcej.08we295
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Cracking in Drying Nanoparticle-Polymer Coatings at High Peclet Numbers

Abstract: We provide experimental evidence that spontaneous cracking in silica-poly(vinyl alcohol) aqueous suspensions is significantly suppressed at high Peclet numbers (Pe). The cracking event in drying suspension coating was quantified by measuring numbers of nucleation points per unit area from acquired time-lapse video images. Direct imaging revealed that increases in Pe, i.e. the film shrinkage rate relative to the particle diffusion rate, postponed the secondary crack nucleation and the inter-crack connection to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Instead, the crack formation may be generated by the nucleation of new cracks, for which the crack spacing does not only depend on lm thickness, but also on drying rate and initial defect concentration. [47][48][49][50] This quantitative deviation between the data and the results predicted by eqn (2) indicates that the elastic fracturing model is too simplistic to adequately capture the behavior of the (organo)silica thin lms in a broad range of regimes. Thus, a new, unied theory is required to explain these different data for diverse systems.…”
Section: Crack Spacingmentioning
confidence: 90%
“…Instead, the crack formation may be generated by the nucleation of new cracks, for which the crack spacing does not only depend on lm thickness, but also on drying rate and initial defect concentration. [47][48][49][50] This quantitative deviation between the data and the results predicted by eqn (2) indicates that the elastic fracturing model is too simplistic to adequately capture the behavior of the (organo)silica thin lms in a broad range of regimes. Thus, a new, unied theory is required to explain these different data for diverse systems.…”
Section: Crack Spacingmentioning
confidence: 90%
“…Experiments conducted by Yamamura et al gives us a reference that paste with high Peclet number is less likely to have brittle crack. 26 In conclusion, the nano-paste shows high sinter activity but suffers from crack formation during drying at low temperature, while the micro-paste shows sufficient drying but they form only a low number of unstable sintering necks. Therefore, trading off between the paste packing density and particle size, which is in turn dependent on the mixture ratio, it becomes vital to get a paste with no-cracks and displaying an enhanced mechanical stability.…”
mentioning
confidence: 86%
“…Numerous studies have been reported on crack‐morphology control via air blowing, 35 electrostatic interactions among dispersing solids, 36 the hydrophilic/hydrophobic surface patterning of the substrate, 37,38 the addition of soft particles that deform to shrink pores between particles, 39‐41 constrained geometry, 42 and evaporation on elastomeric or liquid substrates on which the film shrinkage is no longer hampered by the adhesion on the substrate 28,43 . However, it is not clearly evident how the adsorbing/nonadsorbing nature of polymeric additives on particle surfaces resist crack propagation.…”
Section: Introductionmentioning
confidence: 99%